Vlad, the fabulous vampire - Drago, Flavia Z. (Drago, Flavia Z. World of Gustavo., 2023)
"Vlad is a vampire with the misfortune of having rosy cheeks that--gasp!--make him look abysmally alive. But being the fabulous vampire that he is (and hoping to avoid rejection), he hides his rosy complexion behind elaborate vampire outfits in traditional black. That is, until he finds out that his best friend has a pink secret of her own"--OCLC.